Valuation as destruction? The social effects of valuation processes in contested marine spaces. (November 2018) - Šunde, Charlotte; Sinner, Jim; Tadaki, Marc; Stephenson, Janet; Glavovic, Bruce; Awatere, Shaun; Giorgetti, Annabelle; Lewis, Nick; Young, Aneika; Chan, Kai
Abstract: Valuation encompasses far more than the practice of estimating the financial value of environmental services and changes. It extends to almost any socio-political process in which local actors seek to shape the development of their places and environments by describing what matters about these places. This paper draws on diverse engagements with participants involved in high-profile marine development decisions in New Zealand to examine value-articulating institutions (VAIs), i.e., the formal and informal ways that values of affected parties are elicited, received and evaluated by decision-makers. Our study shows that formal VAIs can be alienating for many participants, demanding huge investments of time and personal sacrifices, demoralising members of communities when their local knowledge and expertise is delegitimised. Such processes can leave communities shaken, conflict-riven and unhappy, and undermine the legitimacy of democratic institutions. All VAIs are imperfect – using informal along with formal VAIs can provide alternative spaces for people to present and describe their values. The paper describes in situ experiences that provide an informal alternative to more formal VAIs. Highlights: Valuation for decision-making can create a destructive path through communities. All value articulating institutions are imperfect. Practice should be transparent, democratic and open to new ways to receive values. In situ experiences can be an effective way to receive intangible values.